Trends in Bone Morphogenetic Protein Usage since the U.S. Food and Drug Administration Advisory in 2008: What Happens to Physician Practices When the Food and Drug Administration Issues an Advisory?. (June 2014) - Mckie, Janay; Qureshi, Sheeraz; Iatridis, James; Egorova, Natalia; Cho, Samuel; Hecht, Andrew
Study Design: Retrospective cross-sectional study of spinal procedures from 2002 to 2010 using the Nationwide Inpatient Sample database. Objective: To determine the patterns of bone morphogenetic protein (BMP) usage in fusion surgery before and after the U.S. Food and Drug Administration (FDA) 2008 advisory for the anterior cervical spine to understand how advisories affect U.S. physician practices. Methods: Procedures were identified through International Classification of Diseases, Ninth Revision procedure codes and were plotted over time based on fusion procedure type, site, and area of fusion. U.S. national trends were approximated by polynomial regression analysis. Results: The majority of the data trends of BMP usage reflect a second-order polynomial model. BMP usage in anterior cervical spine fusion procedures plateaued during the fourth quarter of 2007. The most apparent change in trend was noted in BMP usage pre- and postadvisory in the analysis of anterior cervical spine fusions. BMP percentage of use decreased in this area by 5% from the time of the FDA advisory to the fourth quarter of 2010. Conclusions: The decrease in BMP usage in anterior cervical spinal fusion procedures coincided with the timing of the FDA advisory. The fact that BMP continued to be used in cervical spine fusion procedures, even at lower rates, despite the advisory, may reflect the availability of new clinical information that could lessen complications (i.e., lower BMP dose, perioperative steroids, BMP containment). Furthermore, factors like the natural ceiling effect of use or demand for new technology, complications, prohibitive institutional costs, access to information, and insurance compensation may have all contributed to the BMP usage trends observed.